2018
DOI: 10.1017/s104161021800100x
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with self-rated frailty in older adults from an outpatient clinic: a prospective study

Abstract: It appears that depression with SSRI is associated to frailty, and this association cannot be explained only by antidepressant use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 41 publications
(60 reference statements)
3
33
1
12
Order By: Relevance
“…Of note, results were only partially attenuated when using the modified CESD-10, which excluded fatigue-related items. Although depressive symptoms are correlated with increased risk of reduced functional ability [41][42][43], accurate early detection of depression remains challenging, especially for older adults who do not openly disclose their emotional status to their physician. Future studies should examine whether reporting lower energy may be an accurate indicator of underlying depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, results were only partially attenuated when using the modified CESD-10, which excluded fatigue-related items. Although depressive symptoms are correlated with increased risk of reduced functional ability [41][42][43], accurate early detection of depression remains challenging, especially for older adults who do not openly disclose their emotional status to their physician. Future studies should examine whether reporting lower energy may be an accurate indicator of underlying depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used instruments were the Center for Epidemiologic Studies-Depression (CES-D) and the Geriatric Depression Scale (GDS). Most of the studies whose samples comprised patients clinically diagnosed with depression were crosssectional [41][42][43][44][45][46] while a few were longitudinal 47,48 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that the presence of depression at baseline predicted frailty 37,48 . Both studies investigated depression together with the use of antidepressants and concluded an association with frailty after the follow-up period.…”
Section: Depression As a Predictor Of Frailty Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Like frailty, late-life depression is an independent predictor of geriatric syndromes (e.g. falls, frailty) as well as disability, hospitalization, institutionalization, and death [19][20][21]. Several meta-analyses have shown that depression is an independent risk factor for the onset of hypertension, diabetes, stroke, heart disease, Alzheimer's disease, and cancer [19].…”
Section: Introductionmentioning
confidence: 99%